Consent in the psychotherapy setting - Catanesi, Roberto; Scapati, Francesco; Greco, Oronzo (Medicina e Morale, 1988)
In this way, the issue of consent to health treatment becomes one of the fundamental problems of everyday medical practice, serving as an indispensable link between the physician's power to treat and the patient's personal right to be the manager of his or her own mental and physical health.